Strengthening Southern Africa’s NDCs to Bolster Farmers’ Interests - Chevallier, Romy; Mabuza, Majola; Thornton, Philip K.; Cramer, Laura K. (South African Institute of International Affairs, 2021)
Agriculture and other land-use sectors play a major role in the global response to climate change – as a large source of greenhouse gas (GHG) emissions, as a carbon sink, and as a sector vulnerable to climate extremes and variability. Nationally Determined Contributions (NDCs) are important policy instruments under the Paris Agreement that guide national climate actions in the near to short term. While most Southern African countries have included agriculture in their current NDCs, many lack sector-specific, quantifiable commitments to drive targeted action. In addition, few NDCs in the region have detailed information on the support needed to accomplish these plans, or the necessary governance mechanisms. Countries are expected to update and revise their NDCs every five years. This means that their contents can be strengthened and interested stakeholders can engage in the review process. Farming stakeholders can leverage these processes to ensure that the needs of their constituencies are integrated. The extent to which the agricultural sector can contribute to the effective implementation of the NDC targets will depend on how various stakeholders, specifically farmers, are supported in their transition to low-emission, climate-resilient development pathways.